(a + 2b)(a + 2b)
3a(b+c)+2b(b+c)
2s-2b= a+b+c-2b simplified that would be a+c-b.
Whan a = 2 and b = 6, 5a + 2b = 5*2 + 2*6 = 10 + 12 = 22
-(2b - 1)(4b^2 + 2b + 1)
-8
(2b - 5)(b + 7)
Taking it step by step: 2b - b - 10 = -13 b - 10 = -13 b = -13 + 10 b = - 3
To factor the expression 3ab + 3ac + 2b^2 + 2bc, we first look for common factors among the terms. We can factor out a 3a from the first two terms, and a 2 from the last two terms. This gives us 3a(b + c) + 2(b^2 + bc). Next, we notice that we can factor out a b from the second term in the second parenthesis, giving us the final factored form: 3a(b + c) + 2b(b + c).
4b2-16 =4(b2-4) =4(b+2)(b-2)
5a(a+2b+b²)
=2b
(a + 2b)(a + 2b)
The GCF is a^2b
-b+5b-2b=2b
9a4-b2=36a-2b=2(18-b) But if you meant 9a^4-b^2 it is not possible to factor
3a(b+c)+2b(b+c)